UNGKAPAN KASIH SAYANG DALAM KARYA LUKIS DEKORATIF - PRIH ARIFIN, Drs. Syafwan, M.Si, Dra.Zubaidah, M.Pd (Universitas Negeri Padang, 2015)
Human beings have unlimited imagination. Imaginations of the people try to make it come true, but sometimes make people complacent imagination and live in their fantasy world. When a person fall in love with something, someone could be not himself and was stuck in the fantasy of their own creation. On the way to achieve a sense of love is not only sweet and feels happy. Terkadangn sadness, disappointment, hurt, and tired of being colorful in the process of achieving a sense of love. It is what lies behind the writer to put it on the painting entitled